Time in remission and low disease activity state (LDAS) are associated with a better quality of life in patients with systemic lupus erythematosus: results from LUMINA (LXXIX), a multiethnic, multicentre US cohort - Manuel Francisco Ugarte-Gil; Guillermo J Pons-Estel; Graciela S Alarcón; Luis M Vila; Gerald McGwin (RMD Open)
Aims To determine whether the proportion of time systemic lupus erythematosus patients achieve remission/low disease activity state (LDAS) is associated with a better quality of life (QoL).Patients and methods Patients from a well-established multiethnic, multicentre US cohort were included: remission: Systemic Lupus Activity Measure (SLAM) score=0, prednisone≤5 mg/day and no immunosuppressants); LDAS not in remission, SLAM score≤3, prednisone≤7.5 mg/day, no immunosuppressants; the combined proportion of time patients were in these states was the independent variable. The endpoints were the Physical and Mental Components Summary measures (PCS and MCS, respectively) and the individual subscales of the Short Form (SF)-36 at the last visit. Linear regression was used to estimate the association between the proportion of follow-up time in remission/LDAS and the SF-36 measures with and without adjustment for possible confounders.Results Four hundred and eighty-three patients were included. The per cent of time on remission/LDAS was associated with better QoL after adjusting for potential confounders; for the PCS the parameter estimate was 9.47 (p<0.0001), for the MCS 5.89 (p=0.0027), and for the subscales they ranged between 7.51 (p=0.0495) for mental health and 31.79 (p<0.0001) for role physical.Conclusions The per cent of time lupus patients stay on remission/LDAS is associated with a better QoL as measured by SF-36.